Cyber Physical Security of Distributed Energy Resources - Luka Strezoski; Zorana Babic; Dejan Milojicic (Energija, Ekonomija, Ekologija)
Huge amounts of data are coming from the electrical grid, through smart meters, smart inverters, and Supervisory Control and Data Acquisition (SCADA) protocols. This makes emerging power systems, and especially distribution grids, heavily dependent on real-time data from the field, as well as on the IT infrastructure for observation and control of field devices. As a consequence, emerging electrical systems are becoming fully digitized, cyber-physical systems with all the accompanying advantages and challenges. Such a power system is called a “Smart Grid”. As all cyber-physical systems, Smart Grids are heavily dependent on Information and Communication Technology (ICT) infrastructure. Therefore, they are highly vulnerable to attacks that can compromise uninterrupted data flow, such as denial of service attacks and interruptions due to natural disasters, cataclysmic events, or wars, as well as due to malicious cyber-attacks.